OptAngle at the SBFT 2024 Tool Competition - Cyber-Physical Systems Track - Babikian, Aren A.; Varro, Daniel (2024 IEEE/ACM International Workshop on Search-Based and Fuzz Testing (SBFT), 2024)
OptAngle is a test generator for autonomous vehicles that leverages meta-heuristic search over a road representation based on relative angles between fixed-size road segments. It derives virtual roads by optimizing for (1) road structure validity, (2) failures during test execution, and (3) test case diversity. We have submitted OptAngle for participation to the Cyber-physical systems testing tool competition at SBFT 2024. Results show that test suites produced by OptAngle often provide high failure rates (wrt. its competitors), despite providing low diversity in detected failures.